2010
DOI: 10.1159/000301577
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Glutenins in Wheat-Dependant, Exercise-Induced Anaphylaxis: Allergenicity and Antigenic Relationships with Omega 5-Gliadins

Abstract: Background: Adults suffering from wheat-dependant, exercise-induced anaphylaxis (WDEIA) develop IgE directed against wheat ω5-gliadins (major allergens for this allergy) and against wheat low-molecular weight glutenin subunits (LMW-GS). However, the ability of LMW-GS to trigger an inflammatory response is still unknown. It also remains to be determined if IgE from these patients bind the same epitopes on LMW-GS and ω5-gliadins or if the epitopes are independent. Methods: WDEIA patients were selected and skin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 45 publications
2
33
0
2
Order By: Relevance
“…All percentages based on total gluten contents. Two recombinant LMW-GS also reacted with IgE antibodies [54] and a subsequent study confirmed the WDEIA-specific antigenicity of LMW-GS [55]. In addition to x5-gliadin, HMW-GS were shown to be the most potent allergens [53] with three predominant epitopes (QQPGQ, QQPGQGQQ, and QQSGQGQ) [49].…”
Section: Causative Proteinsmentioning
confidence: 61%
“…All percentages based on total gluten contents. Two recombinant LMW-GS also reacted with IgE antibodies [54] and a subsequent study confirmed the WDEIA-specific antigenicity of LMW-GS [55]. In addition to x5-gliadin, HMW-GS were shown to be the most potent allergens [53] with three predominant epitopes (QQPGQ, QQPGQGQQ, and QQSGQGQ) [49].…”
Section: Causative Proteinsmentioning
confidence: 61%
“…It seems obvious as the ω-5 gliadin fractions act as the main allergens in WDEIA [18,[32][33][34]. However, ω-5 can be also active in other wheat allergies [21,35].…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in immunoreactivity occurred in spite of overexpression of a/b and some c-gliadin genes. a/b and c-gliadins are less allergenic than x-gliadins (Battais et al 2003;Bouchez-Mahiout et al 2010;Waga et al 2011). However, higher amounts of low immunoreactivity a/b or cgliadins might, theoretically, have a greater effect than lower-amounts of more immunoreactive x-gliadin proteins.…”
Section: Discussionmentioning
confidence: 99%